HUBUNGAN PENGETAHUAN BIDAN TENTANG INFEKSI NOSOKOMIAL DENGAN TINDAKAN PENCEGAHANNYA PADA PASIEN BEDAH SEKSIO SESAREA - Situmorang, Paskah Rina (Universitas Prima Indonesia, 2020)
Nosocomial infection is an infection obtained by patients who are undergoing treatment in a hospital. Nosocomial infections stem from non-invasive measures. Prantara that cause nosocomial infections are microorganisms, medications and the environment. Where, is a factor causing nosocomial infection that is the focus of this study is midwives who are less aware of personal’ hygiene. This study aims to determine the relationship of knowledge of midwives about nosocomial infections with prevention measures in cesarean section surgical patients at Imelda General Hospital Medan. This research is a quantitative study with a correlational research design with Cross Sectional approach, where sampling is done with a total sampling technique with a total of 31 midwives, and data collection is done using a questionnaire. The results of the study of midwife knowledge about nosocomial infections are mostly knowledgeable, 21 people (67.8%), while the majority of prevention measures are good, 19 people (61.3%). The results of the study were tested using the Spearman Rank test to see the relationship between knowledge of midwives about nosocomial infections and their preventive measures in post-cesarean section patients, the results obtained with a probability value (p) = 0.011 (p <0.05), which means there is a relationship where (r) = 0.452, it means that the strength of the relationship is sufficient and this relationship is positive which means that if the midwife's knowledge of nosocomial infection is sufficient, the more sufficient value of infection prevention measures is obtained.